Osteolytic lesions as a presenting sign of acute myeloid leukemia: a case report - Zhang, Jingqian; Mu, Shidai; Cai, Li; Ai, Lisha; Wu, Yaohui (Frontiers in Oncology, 2024)
Osteolytic lesions are infrequently observed in adult patients with acute myeloid leukemia (AML). This report details the case of a 66-year-old male patient who presented with myeloid sarcoma(MS), osteolytic lesion and pancytopenia. Effective treatments were delayed due to diagnostic challenges and the rapid progression of the disease. It is essential to consider AML in the differential diagnosis when faced with a patient presenting osteolytic lesions and pancytopenia.